Badanie Stateczności i Optymalizacja Kształtu Sprężystości Utwierdzonego Pręta Rozciąganego - Gajewski, A.; Palej, R. (Engineering Transactions, 1974)
The paper presents a solution of the problem of stability and optimization of a cantilever rod acted on by a tensile force at its free end. The force is assumed to change the direction and the point of application in the process of buckling; its behaviour is determined by four parameters. The problem of stability is based mainly on the statical stability criterion; critical forces. are calculated from the corresponding transcendental equation. The problem of optimization is solved in the case of conservative loading by variational methods. Numerous graphs illustrate the results derived in the paper.